Integrating Character Education Into English Language Teaching - Ratnawati, Ratnawati; Munandar, Aris; H, Nurhikmah; Sulastri, Sulastri (Universitas Pahlawan Tuanku Tambusai, 2024)
This article entitled Integrating Character Education into English Language Teaching. This article explores the integration of character education into English language teaching, emphasizing its significance in fostering both academic and moral development among students. Utilizing a library research methodology, the study compiles data from various sources, including books, journal articles, and online publications, to illustrate the importance of character education in contemporary educational practices. The findings reveal that character education not only enhances students' language proficiency but also cultivates essential moral values and ethical behaviours necessary for responsible citizenship. Furthermore, it outlines effective strategies for integrating character education into English language curricula, including lesson planning, engaging classroom activities, and comprehensive evaluation methods. By embedding character education within English language learning, educators can significantly contribute to the holistic development of students, preparing them to navigate the complexities of a globalized society with integrity and empathy.